Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1007/s002590050036
|View full text |Cite
|
Sign up to set email alerts
|

Technetium-99m labelled antimicrobial peptides discriminate between bacterial infections and sterile inflammations

Abstract: The aim of this study was to select technetium-99m labelled peptides that can discriminate between bacterial infections and sterile inflammations. For this purpose, we first assessed the binding of various 99mTc-labelled natural or synthetic peptides, which are based on the sequence of the human antimicrobial peptide ubiquicidin (UBI) or human lactoferrin (hLF), to bacteria and to leucocytes in vitro. In order to select peptides that preferentially bind to bacteria over host cells, radiolabelled peptides were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
129
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(138 citation statements)
references
References 20 publications
4
129
0
1
Order By: Relevance
“…Binding of the 99m Tc-labeled phages P22 and E79 to host bacteria were reduced in the presence of the non-ionic detergent Tween-80, a detergent that disrupts lipid-lipid and lipid-protein interactions (4). As shown in Figure 2 the addition of Tween-80 to the incubation buffer reduced the binding of 99m Tc-P22 to its host S. enterica to levels observed for the non host bacteria, P. aeruginosa and E. coli, while having no influence on binding to the non host bacteria.…”
Section: Binding In the Presence Of Tween-80mentioning
confidence: 99%
“…Binding of the 99m Tc-labeled phages P22 and E79 to host bacteria were reduced in the presence of the non-ionic detergent Tween-80, a detergent that disrupts lipid-lipid and lipid-protein interactions (4). As shown in Figure 2 the addition of Tween-80 to the incubation buffer reduced the binding of 99m Tc-P22 to its host S. enterica to levels observed for the non host bacteria, P. aeruginosa and E. coli, while having no influence on binding to the non host bacteria.…”
Section: Binding In the Presence Of Tween-80mentioning
confidence: 99%
“…In all radiopharmaceuticals, antimicrobial peptides that attach directly to bacteria are preferred over pharmaceuticals that have an indirect approach (such as binding to leukocytes or antigranulocyte antibodies) [22]. Among the peptides, 99m Tc-UBI 29-41 scans have shown the most promising results for differentiation between infection and inflammation in animal models [11,12,30] and also in limited human studies [22].…”
Section: Resultsmentioning
confidence: 99%
“…The most promising ones among them are 99m Tc-labeled cationic antimicrobial peptides originating from ubiquicidin (UBI), which remarkably bind to microorganisms [10,11]. These radiolabeled antimicrobial peptides result in the rapid visualization of Gram-positive and Gram-negative bacterial infections [12] and fungi [10], with the least accumulation at sites of sterile inflammation [11]. Furthermore, 99m Tc-UBI 29-41 has been used to monitor the effectiveness of treatment of experimental infections in animals [13].…”
Section: Introductionmentioning
confidence: 99%
“…The Coordinated Research Project (CRP) established by the IAEA over the past decade has encouraged the evaluation of UBI as an effective tracer. Studies under the CRP and others have reported UBI to exhibit a high labelling efficiency > 90%, good stability, rapid uptake and clearance via the kidneys, excellent ability to detect infection focus and its differentiation from sterile inflammation as well as therapy response assessment [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Tc-UBI 29-41 scintigraphy of a 38-year-old man in whom posttraumatic osteomyelitis of the right tibia was suspected.…”
Section: Discussionmentioning
confidence: 99%